(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article reveals the phenomenology of loneliness and depression, studies the main forms, levels of manifestation of these phenomena, the conditions for their occurrence and development, features of manifestation in student youth. It was found that the situation of compulsory isolation leads to an increase in the level of loneliness, depression and, as a result, can negatively affect the psychological health of young people. It has been statistically proven that loneliness in a situation of compulsory isolation can be considered as a factor in the development of depressive mental states, the occurrence of depresive disorders. The spread of depressive mental states was noted.